Pembuatan Penghitung Jumlah Mobil Otomatis Berbasis Mikrokontroler ATMega 8535 Menggunakan Sensor Ultrasonik - Riko Dede Hardiyanto; Adian Fatchur Rochim; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Car drivers often experience difficulties to park their cars in the parking lot there is a slot or an empty space with a limited number. For example, some parking places such as shopping centers, apartments and hotels. To determine the state of the parking spaces have been filled or not it is necessary to update the conditions in the room. The purpose of this thesis is to create a functioning device calculates and displays the number of entrances. A number of automatically calculating devices have been made. General description of the device is designed to use the SRF04 ultrasonic sensor, microcontroller ATMega8535, and buzzer. SRF04 ultrasonic sensors as detecting obstructions between the ends of the door with the barrier wall and counting. With the existence of this device in the state of the room can be determined easily and saves time.